1987
DOI: 10.1128/jvi.61.5.1586-1592.1987
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of 2',5'-oligoadenylates in encephalomyocarditis virus-infected mice

Abstract: Levels of 2',5'-oligoadenylates (2-5A) in various tissues of murine encephalomyocarditis virus (EMCV)infected mice were determined and compared with those found in pathogen-free mice and in mice treated with the interferon inducer poly(I) * poly(C). In control, pathogen-free mice, liver, spleen, brain, and kidney tissues possessed levels of 2-5A below 1 pmol/g of tissue, demonstrating that 2-5A was not a major component of uninfected mouse tissue. All control tissues had low basal levels (0.3 to 2.0 pmol/h per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
9
0
1

Year Published

1990
1990
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 38 publications
1
9
0
1
Order By: Relevance
“…In the absence of infection, however, RNase L deficient mice display significantly increased longevity, potentially due to the lack of chronic low level activation of OAS proteins by cellular dsRNAs 37 . Indeed, RNA extracted from various cell types weakly activates OAS1 in vitro 38 , consistent with detectible 2-5A in uninfected tissues 39 . In addition, recent work demonstrated that cellular RNAs activate OAS proteins in the absence of RNA editing by ADAR1 12 .…”
Section: Discussionsupporting
confidence: 64%
“…In the absence of infection, however, RNase L deficient mice display significantly increased longevity, potentially due to the lack of chronic low level activation of OAS proteins by cellular dsRNAs 37 . Indeed, RNA extracted from various cell types weakly activates OAS1 in vitro 38 , consistent with detectible 2-5A in uninfected tissues 39 . In addition, recent work demonstrated that cellular RNAs activate OAS proteins in the absence of RNA editing by ADAR1 12 .…”
Section: Discussionsupporting
confidence: 64%
“…Enzyme measurements of 2-5A nucleases have mainly relied on short substrates unable to activate RNase L, which requires oligoadenylates of trimer length and above [18,[40][41][42][43][44]. We used oligoadenylates of tetramer length and above in our assays, thereby increasing the significance with regard to the 2-5A system.…”
Section: The 2-5a Nuclease Assaymentioning
confidence: 99%
“…Also, the reaction products have mainly been resolved by HPLC using reverse-phased C 18 columns or thin-layer chromatography with PEI-Cellulose, in which the former has been used for production purposes. Likewise, many 2-5A nuclease assays have been reported [18,[40][41][42][43]. They rely on very short 2′-5′ oligoadenylate substrates, especially the 2-5A core dimer ApA, which despite being commercially available, is not biologically relevant in the sense that oligoadenylates of a minimum of three AMP moieties (i.e.…”
mentioning
confidence: 99%
“…EMCV is a (+)ssRNA member of the Picornaviridae family 121 that replicate through partially dsRNA intermediates (Carocci and Bakkali-Kassimi 2012). Infection 122 has been shown to cause accumulation of 2-5A, and viral replication is sensitive to the OAS/RNase 123 L pathway (Hearl and Johnston 1987;Zhou et al 1997). As oligoadenylate synthetases bind viral 124 dsRNA, the RNA activators in EMCV-infected cells are believed to be the viral replicative 125…”
Section: Removal Of Alternative Splice Site Alters Oas1g Expression Amentioning
confidence: 99%